A case report to manage raised uterine artery P.I. associated IUGR with ayurveda intervention - Bajpai, Nidhi; Roy, Anuradha; Rai, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
IUGR is defined as a rate of fetal growth that is less than normal for the expected growth potential of a specific infant. This is a case report of IUGR associated with raised uterine artery Pulsatility index (P.I.) with no other abnormalities. In present case holistic approach of Ayurveda with proper garbhini paricharya (antenatal care) and management principle of garbhakshaya (growth restriction) was acquired. The obstetric scan revealed decreased abdominal circumference and falling growth parameters with raised mean P.I. with high resistant flow in uterine artery. Ayurvedic intervention Ksheerbasti (enema of milk infused drugs) with Medhya drug (drugs which are beneficial for brain functioning) and diet with brinhan(anabolic nature) and garbhaposhak (beneficial for the fetus) actions were given. The outcome was evaluated as P.I. becomes normal and significant improvement in other growth parameters of fetus like AC, EFBW.